Computational Studies of Fullerene Derivatives as Pesticide Captors - Souza, Isis de Castro; Gonçalves, Arlan da Silva (Orbital: The Electronic Journal of Chemistry, 2019)
The use of pesticides in tropical countries such as Brazil has grown resulting in alarming health damage statistics, deaths and environmental pollution. Considering its potential risk and the difficulty on detecting their residues instantaneously in field, six fullerene derivatives were planned using semiempirical calculations and molecular docking to understand its potential as adsorbents and captors of agricultural organophosphate (Ops) pesticides. As Ops were selected acephate, cadusafos, chlorpyrifos, dimethoate, fenitrothion, phenthoate, malaoxon, malathion, methyl-parathion and terbufos. The proposal 4 had the best results and between the Ops, fenitrothion presented the best results, followed by malathion, malaoxon, phentoate and methyl-parathion. DOI: http://dx.doi.org/10.17807/orbital.v11i1.1215